The kitchen front : a novel - Ryan, Jennifer (Jennifer L.) (New York : Ballantine Books, 2021)
"In WWII Britain, a BBC radio program called The Kitchen Front is putting on a cooking contest in an effort to help housewives with food rationing--and the grand prize is a job as the program's first-ever female co-host. For four very different women, winning the contest presents a crucial chance to change their lives."--
Keywords: World War, 1939-1945 -- Great Britain -- Fiction; World War, 1939-1945 -- Women -- Great Britain -- Fiction; Cooking -- Competitions -- Fiction; Historical fiction; War fiction